Short‐term effects of organic matter and compaction manipulations on soil temperature, moisture, and soil respiration for 2 years in the Oregon Cascades. Issue 1 (17th November 2022) - Gallo, Adrian C.; Holub, Scott M.; Littke, Kim; Lajtha, Kate; Maguire, Doug; Hatten, Jeff A.
Abstract: Understanding the factors controlling nutrient dynamics can help guide forest management plans to promote their long‐term productivity. We used experimental treatments with three levels of biomass removals and two levels of compaction to monitor the impacts to soil biophysical characteristics in an intensively managed forest. Soil temperature, moisture, and respiration observations began 6 mo after treatment installation completion and continued for 2 yr. Compaction had few consistent significant effects on measured variables, and there were negligible differences in volumetric soil water content between whole tree (WT) and bole only (BO) harvesting. Compared with BO, the 10‐cm average and maximum growing season temperatures in WT significantly increased by 1.2 and 2.5 °C, respectively. The effects of WT removals resulted in whole profile (10–100 cm) increases in the average and maximum growing season soil temperatures. The WT removals resulted in an increase of 1.4 times more soil growing degree days (SGDD) at 10 cm and 1.6 times more at 100 cm compared with BO. Despite favorable temperature and moisture conditions, differences in soil respiration could not be explained by biomass or compaction treatments. The uncut reference forest was consistently cooler and drier, but respired more CO2 throughout both years of observation compared with treated areas. The large physical disturbance of forest harvesting on the site likely masked any incremental treatment differences by homogenizing the microbial response in the ensuing 2‐yr study period. Future research should continue to investigate whether these soil biophysical changes influence site productivity or more sensitive indices of soil C dynamics. Core Ideas: Bulk density increased 16–23% but compaction had no influence on soil moisture or soil respiration. As more biomass was removed, average growing season temperatures increased significantly from 10 to 100 cm in depth. At the 100‐cm depth whole tree plus forest floor removals had three times more soil growing degree days. The uncut reference forest was consistently cooler and drier, but respired more CO2 throughout the study period. The intense and temporally recent harvest disturbance obscured differences in soil respiration between treatments.